ANALYSIS OF PROTEIN ISOLATE FROM QUINOA (CHENOPODIUM QUINOA WILLD) - A, Toapanta; C, Carpio; R, Vilcacundo; W, CARRILLO (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of this study was to obtain protein isolate from quinoa using alkaline pH at different pHs of precipitation and to analyze protein isolate with electrophoresis. Methods: Quinoa protein isolates were obtained using isoelectric precipitation method at different pHs. Proteins were analyzed using electrophoresis native-polyacrylamide gel electrophoresis (PAGE) and sodium dodecyl sulfate - PAGE. Results: A yield of 6.29% of protein isolate of defatted quinoa at pH 4.0 was obtained. The content of protein isolate was higher than 64% in all pH assays. Globulins and albumins in protein isolate at different pHs were observed. One band near 130 kDa was found. A band with MW 60 kDa corresponding to 7S globulin was found. The bands, MW 33-36 kDa and MW 20-22 kDa, correspond to 11S globulin. Bands less to 15.4 kDa correspond to albumins. Conclusions: Quinoa is a good source of proteins. Globulins and albumins were identified in the quinoa protein isolate. Keywords: Quinoa, Globulins, Albumins, Polypeptides, Protein isolate.